2019
DOI: 10.1111/ane.13192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk of occult cancer in stroke

Abstract: Objectives: Cancer is associated with higher risk of stroke. Whether this translates into higher risk of cancer in stroke of an extent calling for cancer screening in stroke is unclear. We investigated prevalence and risk of occult cancer in stroke compared to the background population without history of stroke. Materials and methods: All patients >40 years of age with incident stroke in Denmark 2003-2015 were identified through the Danish Stroke Registry (n = 85 893) and matched 1:10 on age and sex to the Dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Additionally, cancer influences the coagulation system and therefore may play a role in causing the ICH, and therefore ICH may even be a first symptom of an underlying malignancy. 24 , 25 In the Dutch hospital-based cohort, the percentage of vascular deaths was higher reaching 70%, whereas in the population-based cohort the percentage of vascular deaths was similar to our cohort with 29.8%. 6 , 21 Cause of death was not reported in the Finnish study.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, cancer influences the coagulation system and therefore may play a role in causing the ICH, and therefore ICH may even be a first symptom of an underlying malignancy. 24 , 25 In the Dutch hospital-based cohort, the percentage of vascular deaths was higher reaching 70%, whereas in the population-based cohort the percentage of vascular deaths was similar to our cohort with 29.8%. 6 , 21 Cause of death was not reported in the Finnish study.…”
Section: Discussionsupporting
confidence: 63%
“…The registries and the descriptions of variables used for the analyses in this study have previously been presented in detail 1 . In brief, we included only patients with a first‐time stroke (ischemic or hemorrhagic).…”
Section: Methodsmentioning
confidence: 99%
“…Almost three percent of patients admitted with acute stroke in Denmark harbor occult cancer which will become manifest within a year after stroke. It is 50% more than in the general population without stroke 1 . The risk for harboring occult cancer in stroke patients, therefore, is a matter of concern.…”
Section: Introductionmentioning
confidence: 99%
“…Various radio- and chemotherapeutic agents may affect the development and progression of cardiovascular disease ( Arthurs et al, 2016 ; Navi et al, 2015 ; Zöller et al, 2012 ; Zhang et al, 2021 ). Further, several studies have indicated a high prevalence of occult cancer in patients with cardiovascular disease and reported that it is important to identify cancer risk factors as it may aid in developing new and effective preventive strategies ( Corraini et al, 2018 ; Tybjerg, Skyhøj Olsen & Andersen, 2020 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%